Bioenergy basics for competitive training in elite swimming sport - Solomatin, V. R.; Bulgakova, N. Z. (Theory and Practice of Physical Culture, 2018)
bjective of the study was to analyze the competitive training model benefits in the modern elite swimming sport; systematize bodily physiological responses to distance-specific workloads versus maximal aerobic and anaerobic capacities of elite swimmers. The 16-18 year-old Candidate Masters and Masters of Sport (42 males and 22 females) were subject to the study. The sample`s performance was tested by maximal-speed 50/100/200/400m front and back crawl, butterfly or breaststroke swimming, with the training process effects tested by the gas exchange rates. The study found benefits of the maximal-speed one-time 100/400m optional-style swimming for the aerobic capacity building in elite junior swimmers. To speed up the anaerobic capacity building process, the elite swimmers of both sexes tested with relatively high VO2max and ExcCO2 indices are recommended the one-time maximal-speed optional-style 50-400m swimming exercise; whilst the senior elite swimmers tested with the relatively low VO2max and ExcCO2 indices are recommended to swim 100/200m in the same way. For the functionality and strength building purposes, the above method may be combined with the 50-400m butterfly swimming.